Effects Of Fusaric Acid Treated And Gamma Irradiated Protocorm-Like Bodies (PLBs) Of Dendrobium Hybrid Against Fusarium Proliferatum And Fusarium Oxysporum - Sangu, Sangeetha Siva (2017)
Dendrobiums are popular cut flowers in the floriculture and medicinal fields but are prone to yield loss due to diseases caused by fungi. The aim of this research was to utilise the mycotoxin, fusaric acid (FA) and gamma irradiation treatment on Dendrobium hybrid (Dendrobium Waipahu Beauty × Dendrobium Burana White Big Flower) to produce cultivars that are resistant towards Fusarium proliferatum and F. oxysporum.